2022
DOI: 10.1007/s00134-022-06726-w
|View full text |Cite
|
Sign up to set email alerts
|

Major candidate variables to guide personalised treatment with steroids in critically ill patients with COVID-19: CIBERESUCICOVID study

Abstract: Purpose Although there is evidence supporting the benefits of corticosteroids in patients affected with severe coronavirus disease 2019 (COVID-19), there is little information related to their potential benefits or harm in some subgroups of patients admitted to the intensive care unit (ICU) with COVID-19. We aim to investigate to find candidate variables to guide personalized treatment with steroids in critically ill patients with COVID-19. Methods Multicentre, observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…Another recently published study demonstrated that mortality rose in patients ≥ 80 years [ 35 ]. A recent large multicenter observational study in the ICU-admitted patients found a survival benefit in patients > 60 years [ 36 ]. The timing of GCs prescription is another valid question: an early administration represents other clinical scenarios that could modulate the benefits conferred by GCs.…”
Section: Know Your Patientmentioning
confidence: 99%
See 4 more Smart Citations
“…Another recently published study demonstrated that mortality rose in patients ≥ 80 years [ 35 ]. A recent large multicenter observational study in the ICU-admitted patients found a survival benefit in patients > 60 years [ 36 ]. The timing of GCs prescription is another valid question: an early administration represents other clinical scenarios that could modulate the benefits conferred by GCs.…”
Section: Know Your Patientmentioning
confidence: 99%
“…The timing of GCs prescription is another valid question: an early administration represents other clinical scenarios that could modulate the benefits conferred by GCs. Remarkably, in the CIBERESUCICOVID study [ 36 ], it was revealed that GCs increased mortality in the ICU-admitted patients when the therapy was initiated < 7 days of symptoms onset. Regarding early GC administration in ICU patients, the results are controversial; an early administration seemed beneficial [ 37 ] but patients receiving GCs with a 48 h delay were not discarded [ 36 ].…”
Section: Know Your Patientmentioning
confidence: 99%
See 3 more Smart Citations